(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This article implements an Android application-based speed and direction control of a DC motor using a Bluetooth module. This setup consists of two basic primary elements communicating with each other: i) the Bluetooth of the smartphone, which is connected to the Arduino microcontroller, IC, and DC motor interfaced with a L293D motor driver IC; and ii) a Bluetooth module (HC-05). The Android application on a smartphone sends or receives data to or from the microcontroller using Bluetooth. An Android application on the smartphone acts as a display panel for the user to send, receive, or view the output and input of the DC motor. The display includes a screen showing the commands and responses against each other. The motor can be rotated 0-360 degrees and can even change its direction from left to right until stopped. Thus, this proposed control methodology is applied to control the speed and direction of a DC motor wirelessly.